Prednisone/prednisolone and deflazacort regimens in the CINRG Duchenne Natural History Study. (22nd September 2015) - Bello, Luca; Gordish-Dressman, Heather; Morgenroth, Lauren P.; Henricson, Erik K.; Duong, Tina; Hoffman, Eric P.; Cnaan, Avital; McDonald, Craig M.
Abstract : Objective: We aimed to perform an observational study of age at loss of independent ambulation (LoA) and side-effect profiles associated with different glucocorticoid corticosteroid (GC) regimens in Duchenne muscular dystrophy (DMD). Methods: We studied 340 participants in the Cooperative International Neuromuscular Research Group Duchenne Natural History Study (CINRG-DNHS). LoA was defined as continuous wheelchair use. Effects of prednisone or prednisolone (PRED)/deflazacort (DFZ), administration frequency, and dose were analyzed by time-varying Cox regression. Side-effect frequencies were compared using χ 2 test. Results: Participants treated ≥1 year while ambulatory (n = 252/340) showed a 3-year median delay in LoA ( p < 0.001). Fourteen different regimens were observed. Nondaily treatment was common for PRED (37%) and rare for DFZ (3%). DFZ was associated with later LoA than PRED (hazard ratio 0.294 ± 0.053 vs 0.490 ± 0.08, p = 0.003; 2-year difference in median LoA with daily administration, p < 0.001). Average dose was lower for daily PRED (0.56 mg/kg/d, 75% of recommended) than daily DFZ (0.75 mg/kg/d, 83% of recommended, p < 0.001). DFZ showed higher frequencies of growth delay ( p < 0.001), cushingoid appearance ( p = 0.002), and cataracts ( p < 0.001), but not weight gain. Conclusions: Use of DFZ was associated with later LoA and increased frequency of side effects. Differences in standards of care and dosing complicate interpretation of this finding, but stratification by PRED/DFZ might be considered in clinical trials. This study emphasizes the necessity of a randomized, blinded trial of GC regimens in DMD. Classification of evidence: This study provides Class IV evidence that GCs are effective in delaying LoA in patients with DMD.